Выбор параметров цифрового нечеткого регулятора - Домнин, И.Ф.; Левон, Е.А. (Технічна електродинаміка, 2012)
The operation of the digital fuzzy controller in the control system of a filter compensating device. Defined the parameters for the digital. Describes the dependence of the efficiency of the work of the regulator from the parameters necessary to configure it. Given the vectorial methods of optimization of objective functions of the fuzzy control system of a filter compensating device. It is offered to use optimization methods for the selection of the optimal parameters for setting the digital fuzzy controller.